2014
DOI: 10.1037/a0035962
|View full text |Cite
|
Sign up to set email alerts
|

Genetic complexity of episodic memory: A twin approach to studies of aging.

Abstract: Episodic memory change is a central issue in cognitive aging, and understanding that process will require elucidation of its genetic underpinnings. A key limiting factor in genetically informed research on memory has been lack of attention to genetic and phenotypic complexity, as if “memory is memory” and all well-validated assessments are essentially equivalent. Here we applied multivariate twin models to data from late-middle-aged participants in the Vietnam Era Twin Study of Aging to examine the genetic arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 46 publications
6
40
0
Order By: Relevance
“…This is in line with an earlier study reporting a heritability of 0.36 for word list learning measure including multiple trials (CVLT) 20. However, the first trial of the 16-item word list (CVLT) has been reported to show zero heritability indicating that a single-trial administration of a word list may not be reliable enough to show consistent heritability 21. In our study, the 10-item word list was presented only once but still showed substantial heritability.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with an earlier study reporting a heritability of 0.36 for word list learning measure including multiple trials (CVLT) 20. However, the first trial of the 16-item word list (CVLT) has been reported to show zero heritability indicating that a single-trial administration of a word list may not be reliable enough to show consistent heritability 21. In our study, the 10-item word list was presented only once but still showed substantial heritability.…”
Section: Discussionsupporting
confidence: 90%
“…To address the issue of confounding of genetic influences on episodic memory by genetic influences on GCA, we adjusted all memory measures for GCA prior to the twin analyses (Kremen et al, 2014). The adjusted (residual) scores were then used in the twin analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The second model, the Longitudinal Factor Model , extends our previously described higher-order common pathways model of episodic memory to two measurement timepoints (Kremen et al, 2014), and provides the opportunity to test the invariance of the factor structure across time as well as the stability of the latent phenotypes. As depicted in Figure 1, the identical factor structure is specified to the data from VETSA1 and VETSA2, and the genetic and environmental determinants of all latent factors, and the observed variables are allowed to correlate across time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both represent complex, multidimensional and multi-determined phenotypes with their own complex genetic architectures (Flint & Munafò, 2007; W.S. Kremen et al, 2007; W. S. Kremen et al, 2014; Papassotiropoulos & de Quervain, 2011).…”
Section: Genetics and Neuropsychology: A Merger Whose Time Has Comementioning
confidence: 99%